Pengaruh Lingkungan Sosial dan Locus of Control Terhadap Perilaku Keuangan Generasi Z di Kota Sorong - Fauzan; Hasbiah; Rokhimah (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the influence of hedonistic lifestyle and social influence on the financial behavior of Generation Z in Sorong City, addressing the limited contextual evidence on how lifestyle orientation and social pressure shape young people’s financial decisions in a digital consumption environment.This study employed a quantitative approach with an explanatory associative design. The respondents consisted of 100 Generation Z individuals residing in Sorong City, selected through purposive sampling based on criteria such as active social media use and experience in making personal financial decisions. Data were collected using a closed-ended questionnaire measured with a five-point Likert scale. The data were analyzed using descriptive and inferential statistics, with multiple linear regression conducted through SPSS.The findings indicate that hedonistic lifestyle influences the financial behavior of Generation Z through consumption tendencies oriented toward pleasure, self-image, impulsive buying, and immediate gratification. Social influence also affects financial behavior through group norms, peer pressure, family, community, and social media. Simultaneously, hedonistic lifestyle and social influence contribute to shaping the financial behavior of Generation Z in Sorong City.The findings suggest that financial education for Generation Z should not only emphasize financial literacy, but also address self-control, digital consumption awareness, and social pressure.This study provides contextual evidence from Sorong City by integrating hedonistic lifestyle and social influence as key determinants of Generation Z’s financial behavior